Data communications in shallow water - Busch, A. (2005)
The sea is really a particular environment. Its properties are very typical and it’s why a lot of scientists work on it in order to determine its characteristics. The underwater acoustics is one of the domain which are particularly studied, because of its importance in a lot of applications, civilians and militaries. This is very useful also because the ocean is totally opaque to the electro-magnetic waves. So, the sound results to be the better mean to communicate under the surface of the sea. But, even if it is at the moment the better way for underwater communications, a lot of problems have been encountered as soon as we tried to transmit data. One of the problems encountered is about the distorsion of our data. Indeed, when you send a data under the sea surface, a lot of parameters make that the data received is not the same as the data sent. It is a big problem and we can’t do differently. So, the only way is to process this data after receiving it, trying to do the inverse of what has been done during the communication, and so getting exactly what was sent. When we speak about this, it seems very simple. But the knowledge it requires, about the environment, the communications, for example, is so huge that it rapidly becomes really difficult.